The Seven Sleepers (Ashabul Kahf ) in the Holy Bible and Qur'an : Lessons for Organic Youth Movements - Mohamad Syukri Abdul Rahman; Zikrullah; Mohamad Muhajir; Muhammad Ghazali; Aditya Putra Harwanto (Pustaka Peradaban, 2024)
The role of youth as agents of social change is an integral part of the history of every civilization. One fascinating example of youth role models, often overlooked in historical records, is the story of the Seven Sleepers (Ashabul Kahfi). The tale of the Seven Sleepers and their faithful dog is enshrined in the sacred texts of the Abrahamic religions: Judaism, Christianity, and Islam. This article aims to examine and analyze in depth the epic exemplarity of Ashabul Kahf as presented in the Bible, revered by Christians, and the Quran, considered an authoritative source by Muslims. This study seeks to connect the various examples of exemplary behavior with contemporary youth movements, which seem to lack a guiding framework and roadmap for their actions. The methodology used in this article is a content analysis of two authoritative sources: the Bible and the Quran. The findings of this article suggest that the epic exemplarity of Ashabul Kahf in the Bible and the Quran lies in their integrity as youth who chose to defy an oppressive regime.